Pengaruh Kualitas Pelayanan, CRM dan Citra Merek Terhadap Loyalitas Tamu Menginap di Hotel Horison Ultima Bekasi - Nadia Yuliasti; Verry Cyasmoro (Komunitas Dosen Indonesia, 2023)
This study aims to explain the impact of service quality, Customer Relationship Management (CRM), and brand image on guest loyalty at Hotel Horison Ultima Bekasi. The research adopts quantitative methods and acquires primary data through the distribution of questionnaires to a sample of 100 randomly selected customers from Hotel Horison Ultima Bekasi, utilizing a purposive sampling technique. The data analysis involves employing a multiple linear regression model, as well as conducting classical assumption testing, multiple linear regression testing, coefficient of determination testing, and hypothesis testing using the t-test and f-test. The findings reveal that service quality, CRM, and brand image collectively exert a significant influence on guest loyalty at Hotel Horison Ultima Bekasi. In light of these results, it is recommended that Hotel Horison Ultima Bekasi concentrates on enhancing these three variables to foster more favorable perceptions and cultivate a sense of loyalty among its guests